2013
DOI: 10.1615/plasmamed.2014008540
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Plasma Increases Expression of Wound Healing Related Genes in a Keratinocyte Cell Line

Abstract: The application of physical plasma in medicine has great potential in wound healing. Due to the generation of reactive oxygen and nitrogen species (ROS, RNS), emission of UV radiation and the generated electric fields can be used to stimulate epithelial and immune cells. To understand the processes on a molecular level the human keratinocyte cell line HaCaT was treated with a nonthermal atmospheric pressure argon plasma jet (kinpen). Subsequently, cellular RNA was isolated to conduct a quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…Moreover, apoptotic effects were nearly negligible at all treatment times. In a previous study, it was demonstrated that incubation of cells with plasma-treated medium resulted in an acute death rate under 10% in HaCaT cells (49), which was confirmed by the present data from viability assays. However, the magnitude of apoptosis is strongly dependent on the investigated cell type.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, apoptotic effects were nearly negligible at all treatment times. In a previous study, it was demonstrated that incubation of cells with plasma-treated medium resulted in an acute death rate under 10% in HaCaT cells (49), which was confirmed by the present data from viability assays. However, the magnitude of apoptosis is strongly dependent on the investigated cell type.…”
Section: Discussionsupporting
confidence: 90%
“…10D). Interestingly, VEGF expression was indeed shown to be increased by plasma treatment in the cellular environment (49). This growth factor has multiple effector cells among which are keratinocytes and endothelial cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It signals via RhoA–ROCK and Nod2–NF‐κB signalling pathways and is associated with increased cell motility . We also have previously shown a number of growth factors released by keratinocytes following exposure to plasma‐treated medium, suggesting a possible involvement in enhanced skin cell motility for wound healing …”
Section: Resultsmentioning
confidence: 82%
“…Its antibacterial effects are well documented [3,4] and there have been various medical applications such as decontamination of heat sensitive endoscopes and ablation of dental biofilms [5,6]. Preliminary trials showed that plasma application significantly reduced the bacterial load in chronic wounds [7] and potentially stimulated epithelial cells [8,9]. Thus, it seems promising in wound recovery since effective therapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%